2012
DOI: 10.2215/cjn.13081211
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns and Mineral Metabolism Abnormalities in the Cinacalcet Era

Abstract: Summary Background and objectives Prescription patterns for hemodialysis patients with secondary hyperparathyroidism have varied widely since market introduction of cinacalcet. This study examined associations between prescription patterns and subsequent laboratory values. Design, setting, participants, & measurements Using a Mineral and Bone Disorder Outcomes Study for Japanese CKD Stage 5D Patients subcohort, 1716 prevalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…The rise in cinacalcet and intravenous vitamin D analogs prescriptions is consistent with published region-specific data (32,33). Given the recent results of the Evaluation of Cinacalcet Hydrochloride Therapy to Lower CardioVascular Events Trial (34), in which cinacalcet treatment produced only an ambiguous and at most, modest effect on clinical outcomes, it will be interesting to continue to monitor potential changes in SHPT treatments.…”
Section: Discussionsupporting
confidence: 69%
“…The rise in cinacalcet and intravenous vitamin D analogs prescriptions is consistent with published region-specific data (32,33). Given the recent results of the Evaluation of Cinacalcet Hydrochloride Therapy to Lower CardioVascular Events Trial (34), in which cinacalcet treatment produced only an ambiguous and at most, modest effect on clinical outcomes, it will be interesting to continue to monitor potential changes in SHPT treatments.…”
Section: Discussionsupporting
confidence: 69%
“…A recent subcohort study suggested that a combination of 'starting cinacalcet' and 'increased VDRA dose' was associated with better achievement of target iPTH levels than other treatments in cinacalcet-naïve patients [22]. Fukuma et al [23] hypothesized that differences in the mechanisms of action between VDRA and cinacalcet may provide an additive clinical benefit in the management of SPHT.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is often used to counteract hypocalcaemia related to cinacalcet. Thus, the combination use of native vitamin D or its analogs with cinacalcet allows calcium, phosphate and PTH target levels to be achieved simultaneously and greater PTH reduction has been observed using this combination therapy compared to either agent alone (120,121). The OPTIMA study was an open label study which used an algorithm-based adjustment of VDRAs during the dose titration of cinacalcet in patients with moderate to severe SHPT (iPTH 300 -800 pg/ml).…”
Section: Calcimimeticsmentioning
confidence: 99%